What’s On My Mind: Using Social Media To Discuss Stressful Situations - Knight, Jennifer; Bowman, Nicholas; Banks, Jaime; Primack, Brian; Colditz, Jason; Shensa, Ariel (AoIR Selected Papers of Internet Research, 2017)
Evidence suggests that time spent with social media (SM) is positively associated with depression and negatively associated with well-being and life-satisfaction. However, such studies rarely explore how people are using SM in ways that could potentially alleviate depressive symptoms like discussing stress and seeking social support. This study sought to bridge that gap by investigating the types of stressful and emotional situations people discuss on SM. Open-ended data from n = 1,200 participants (n = 1414 utterances) was analyzed using emergent thematic analysis to reveal 10 topic themes: No Discussion (n = 544, 38.4% of utterances), School/Work (n = 237, 16.8%), Daily Personal Struggles (n = 219, 15.5%), Relational Conflict (n = 122, 8.6%), Large Scale Global Issues (n = 91, 6.4%), Deaths/Illness (n = 78, 5.5%), Humorous Complaints (n = 49, 3.5%), Serious Emotional Struggles (n = 42, 3.0%), Missing People/Places(n = 18, 1.3%), and Vaguebooking (n = 18, 1.3%). Our results show that although many users avoid stressful and emotional discussions (perhaps to engage a “positivity norm” online), there are still many people that talk about a wide variety of stressful topics on SM, perhaps implicitly (or even explicitly) seeking self-affirmations and consolation and other forms of social support. In light of debates surrounding SM use and depression, these themes illuminate the potential for SM to function as spaces of social support seeking, such that future research should consider the potential positive mental health potentials as well as the negative.